Vitamin D deficiency in non-scarring and scarring alopecias: a systematic review and meta-analysis - Yongpisarn, Tanat; Tejapira, Kasama; Thadanipon, Kunlawat; Suchonwanit, Poonkiat (Frontiers in Nutrition, 2024)
Background: Numerous studies have linked vitamin D deficiency (VDD) to the pathogenesis of various alopecia disorders.Objective: This study aimed to investigate whether patients with alopecia are more likely to have VDD or lower vitamin D levels than controls, and the prevalence of VDD among patients with certain alopecia disorders. Methods: Electronic searches were conducted using PubMed, Embase, Scopus, and Cochrane Library databases from the dates of their inception until September 2024. Studies that reported data allowing for the calculation of odds ratios, mean differences, or correlation coefficients related to vitamin D levels and alopecia were included, while studies without a confirmed diagnosis of alopecia or those involving patients taking vitamin D supplements were excluded. Results: It was found that 51.94% of patients with alopecia areata (AA), 50.38% of patients with female pattern hair loss (FPHL), 47.38% of patients with male androgenic alopecia (MAGA), 53.51% of patients with telogen effluvium (TE), and 38.85% of patients with primary scarring alopecia had VDD. Compared to controls, AA patients had a pooled odds ratio (OR) of VDD of 2.84 (95% confidence interval: 1.89-4.26, I 2 = 84.29%, p<0.01) and a pooled unstandardized mean difference (UMD) of vitamin D levels of -8.20 (-10.28--6.12, I 2 =74.25%, p<0.01) ng/mL. For FPHL patients, a pooled OR of VDD of 5.24 (1.50-18.33, I 2 =81.65%, p<0.01) and a pooled UMD of vitamin D levels of -15.67 (-24.55--6.79, I 2 =91.60%, p<0.01) ng/mL were found. However, for MAGA, a pooled VDD OR of 4.42 (0.53-36.61, I 2 =88.40%, p<0.01), and a pooled UMD of vitamin D levels of -2.19 ng/mL (-4.07--0.31 ng/mL, I 2 =7.64%, p=0.37) were found. For TE patients, pooled UMD of vitamin D levels of -5.71 (-10.10--1.32) ng/mL were found. Conclusions: People with alopecia frequently have VDD; however, only in patients with AA or FPHL was the association of VDD and decreased vitamin D levels statistically significant compared to control. The findings indicate screening for vitamin D could benefit patients with AA or FPHL, potentially addressing vitamin D deficiency. Further study on vitamin D supplementation as a treatment for alopecia is recommended.